Bioremediation of an aged diesel oil-contaminated Antarctic soil: Evaluation of the “on site” biostimulation strategy using different nutrient sources - Dias, Romina Laura; Ruberto, Lucas Adolfo Mauro; Hernández, Edgardo; Vázquez, Susana Claudia; Lo Balbo, Alfredo; del Panno, Maria Teresa; Mac Cormack, Walter Patricio (International Biodeterioration & Biodegradation)
Under Antarctic conditions, bioremediation processes are highly limited. Although chronically contaminated soils seem to require no bioaugmentation, biostimulation proved to be beneficial although diverse results have been reported in relation to the type of nutrient source and the best experimental design. In this work we evaluated, in ?on site? land plots, the effect that on the hydrocarbon removal and bacterial community structure of a fuel contaminated soil have an inorganic salts mixture, a complex organic matrix (fish meal) and a commercial product listed by the EPA. Also the effect of a surface active compound (Brij700) on biodegradation process was studied. Brij700 did not improve biodegradation in any of the studied conditions but induced relevant changes on bacterial community of soil amended with fish meal. Although fish meal significantly enhanced bacterial counts, this effect was unspecific, drastically changed the bacterial community structure and did not improve hydrocarbon removal. Salts amended systems evidenced a non significant decrease in contaminant concentration. Commercial product caused the higher reduction (49.4%, p<0.05) of hydrocarbons compared with the control system after 45 d of treatment and cause the minor changes in bacterial community, constituting a promising alternative for some hydrocarbon-contaminated Antarctic soil restoration. Fil: Dias, Romina Laura. Ministerio de Ciencia, Tecnología e Innovación Productiva. Agencia Nacional de Promoción Científica y Tecnológica. Fondo para la Investigación Científica y Tecnológica; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en Fermentaciones Industriales. Universidad Nacional de La Plata. Facultad de Ciencias Exactas. Centro de Investigación y Desarrollo en Fermentaciones Industriales; Argentina Fil: Ruberto, Lucas Adolfo Mauro. Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica; Argentina. Ministerio de ...